2020
DOI: 10.3389/fvets.2020.597960
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and Corpus Luteum Blood Flow Evaluation Prior to Uterine Flushing in Llama Embryo Donors

Abstract: The aim of this study was to assess the uterine blood flow (UBF) and corpus luteum blood flow (CLBF) in llamas 8 days post-mating, using color-Doppler ultrasonography (CDU), to determine the possible relationship between vascularization and the presence of an embryo. Adult females ( n = 25) were used to monitor ovarian dynamics by palpation and transrectal ultrasonography until detection of a ≥6 mm growing follicle. Females were randomly assigned to one of two groups: Group I ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The latest Doppler indices differed significantly between women with and without ovarian dysfunction and correlated significantly with markers of ovarian dysfunction, and these results support the use of Doppler ultrasound to detect ovarian dysfunction [17]. Patients undergoing IVF have a Doppler ultrasound of the uterine arteries before the day of egg retrieval, a test that is thought to be associated with success after embryo transfer [18]. Positive effects of acupuncture for infertility may be related to endorphin system inhibition of central sympathetic nerves, altered uterine blood flow and motility, and stress reduction [19].…”
Section: Improve Blood Flowmentioning
confidence: 57%
“…The latest Doppler indices differed significantly between women with and without ovarian dysfunction and correlated significantly with markers of ovarian dysfunction, and these results support the use of Doppler ultrasound to detect ovarian dysfunction [17]. Patients undergoing IVF have a Doppler ultrasound of the uterine arteries before the day of egg retrieval, a test that is thought to be associated with success after embryo transfer [18]. Positive effects of acupuncture for infertility may be related to endorphin system inhibition of central sympathetic nerves, altered uterine blood flow and motility, and stress reduction [19].…”
Section: Improve Blood Flowmentioning
confidence: 57%
“…This fact has lead researchers to generate several hypotheses about the existence of structural and functional differences in the reproductive tract on the left uterine horn that can affect female fertility (Del Campo et al, 1996; Sumar & Adams, 2006; Vaughan & Tibary, 2006). The relationship of vascularization in the uterus of llamas and the presence of an embryo was studied through Colour Doppler ultrasonography (CDU; Zampini et al, 2020); it showed a tendency of a higher blood flow in the presence of a corpus luteum in the left uterine horn compared to the right uterine horn. However, they did not find significant differences in blood flow between both uterine horns irrespective of the location of the corpus luteum in pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…This fact leads to hypothesize that developing embryos on the right side must migrate to the left side to maintain gestation (Sumar & Adams, 2006) or to prevent the systemic luteolytic effect of the left uterine horn (Vaughan & Tibary, 2006). An increase in estradiol‐17β has been demonstrated during early pregnancy (Powell et al, 2007), and its relationship with increased uterine blood flow (Zampini et al, 2020), which is explained by the interaction of the embryo with the uterine lumen (Picha et al, 2013; Tibary et al, 2013). Therefore, we can hypothesize the existence of structural differences between the left and right and the oviduct that may affect female fertility.…”
Section: Introductionmentioning
confidence: 99%
“…All females were examined by transrectal doppler ultrasonography, every other day from Day 6 until Day 18 post-mating; in order to assess the ovulation of the largest follicle after treatment, the development of an accessory CL and the diameter and vascularization of both CLs (the original CL and the accessory CL). The vascularization of both CLs was evaluated as previously described [5,24,25]. Briefly, the transducer was placed over the ovary and three seconds video-clips of the CL vascularization were registered and downloaded.…”
Section: Experimental Designmentioning
confidence: 99%